Does Cooperation in the Laboratory Reflect the Operation of a Broad Trait?. Issue 1 (11th November 2018) - McAuliffe, William H.B.; Forster, Daniel E.; Pedersen, Eric J.; McCullough, Michael E.
Abstract: The Dictator Game, a face valid measure of altruism, and the Trust Game, a face valid measure of trust and trustworthiness, are among the most widely used behavioural measures in human cooperation research. Researchers have observed considerable covariation among these and other economic games, leading them to assert that there exists a general human propensity to cooperate that varies in strength across individuals and manifests itself across a variety of social settings. To formalize this hypothesis, we created an S‐1 bifactor model using 276 participants' Dictator Game and Trust Game decisions. The general factor had significant, moderate associations with self‐reported and peer‐reported altruism, trust, and trustworthiness. Thus, the positive covariation among economic games is not reducible to the games' shared situational features. Two hundred participants returned for a second session. The general factor based on Dictator Game and Trust Game decisions from this session did not significantly predict self‐reported and peer‐reported cooperation, suggesting that experience with economic games causes them to measure different traits from those that are reflected in self‐assessments and peer‐assessments of cooperativeness. © 2018 European Association of Personality Psychology